PERANAN SOSIOLOGI DALAM PENDIDIKAN ALAM SEKITAR: SATU CABARAN - Abdullah, Nurul Hidayah Liew; Ahmad, Jamilah; Hashim, Suhaizal (Online Journal for TVET Practitioners, 2018)
Sociology refers to the field of scientific research on social interactions, organizations, societies, human actions and their consequences and how social influences shape human life. Environment is also a major element in human survival. Human dependence on the environment causes environmental conservation measures to be carried out. The role of sociology is seen as an important medium and must be implemented to ensure that the sustainability of the environment can be realized not only for the benefit of the present generation but for future generations. The increasingly complex human actions and patterns of life have led to various effects on the environment and the people themselves. Therefore, human beings are the dominant environmental users then the human function of the environment needs to be emphasized in order to improve the quality of the environment and its sustainability. Hence, this paper is a review of the role of sociology in Environmental Education (PAS). It is expected that these reviews can help in order to preserve the environment.